2019
DOI: 10.1140/epjd/e2019-100048-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectricity of cold ions in optical lattices

Abstract: We study analytically and numerically the thermoelectric properties of cold ions placed in an optical lattice. Our results show that the transition from sliding to pinned phase takes place at a certain critical amplitude of lattice potential being similar to the Aubry transition for the Frenkel-Kontorova model. We show that this critical amplitude is proportional to the cube of ion density that allows to perform experimental realization of this system at moderate lattice amplitudes. We show that the Aubry phas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(51 citation statements)
references
References 55 publications
(120 reference statements)
5
46
0
Order By: Relevance
“…where the effective momentum p i = 1/(x i −x i−1 ) 2 is conjugated to x i and the kick function is g(x) = − sin x − (ω 2 /K)x. In [19,27], it is shown that this map (2) describes well the actual equilibrium ion positions even when all interactions between ions are taken into account. Let us define the average ion density ν = N/L where L is the number of spatial periods of the optical lattice.…”
Section: System Descriptionmentioning
confidence: 98%
See 4 more Smart Citations
“…where the effective momentum p i = 1/(x i −x i−1 ) 2 is conjugated to x i and the kick function is g(x) = − sin x − (ω 2 /K)x. In [19,27], it is shown that this map (2) describes well the actual equilibrium ion positions even when all interactions between ions are taken into account. Let us define the average ion density ν = N/L where L is the number of spatial periods of the optical lattice.…”
Section: System Descriptionmentioning
confidence: 98%
“…Examples of ion positions for KAM and Aubry phases are given in Appendix Figs. A1, A2 (see also [19,27]). The phase space of the map (2) and the equilibrium ion positions are shown in Appendix tions near the equilibrium positions and then the phonon spectrum and eigenmodes are obtained by matrix diagonalization.…”
Section: Properties Of Phonon Eigenmodesmentioning
confidence: 99%
See 3 more Smart Citations